2023
DOI: 10.1787/c945c24f-en
|View full text |Cite
|
Sign up to set email alerts
|

Informality and Globalisation

Abstract: Photo credits: Cover design by Mélodie Ly Descours (OECD Development Centre) on the basis of images from anurakss, Drop of Light, Ivan Bruno de M, Dejan Dundjerski, KPPWC /Shutterstock.com.Corrigenda to OECD publications may be found on line at: www.oecd.org/about/publishing/corrigenda.htm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Informality is one of the most widespread phenomena in the labour markets of developing countries. It is a structural and multi-dimensional phenomenon, and both the cause and consequence of low-income levels (OECD/ILO, 2019 [1]; OECD, 2023 [2]). Official definitions of informality vary across institutions and countries, but one salient feature applied to define informality for the purpose of this paper is that informal firms and workers often do not pay contributions to social security schemes, such as old-age pensions, health, or unemployment benefits.…”
Section: Figuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Informality is one of the most widespread phenomena in the labour markets of developing countries. It is a structural and multi-dimensional phenomenon, and both the cause and consequence of low-income levels (OECD/ILO, 2019 [1]; OECD, 2023 [2]). Official definitions of informality vary across institutions and countries, but one salient feature applied to define informality for the purpose of this paper is that informal firms and workers often do not pay contributions to social security schemes, such as old-age pensions, health, or unemployment benefits.…”
Section: Figuresmentioning
confidence: 99%
“…Labour informality is so widespread in Latin America that tying transfer benefits to formal labour market participation, which is the salient characteristic of most social protection benefits across Latin America, may risk leaving behind too many of those in need. At the same time, history has shown that countries will not simply grow their way out of informality, which can be part of a vicious circle (OECD, 2024 [26]). Even those LAC countries with a strong growth trajectory, such as Perú, or those with higher per-capita incomes, such as Argentina and Uruguay, still have significant levels of informality.…”
Section: Unclassifiedmentioning
confidence: 99%
See 1 more Smart Citation
“…Informal employment is one type of employment condition on the decent through unacceptable work spectrum ( McCann and Fudge, 2017 )—others include full employment, precarious employment, unemployment, child labour, bonded labour and slavery ( Benach et al , 2010a ). Informal employment is the most common form of employment in the world [International Labour Organization ( ILO), 2018 ], with the agricultural, domestic and construction industries most likely to hire informal labour ( OECD, 2023 ). As such it is important for health promotion to understand its health impact.…”
Section: Introductionmentioning
confidence: 99%
“…Although more common and visible in low- and middle-income countries (LMICs), informal labour has global prominence. In low-income countries, informal employment is reported to account for 89% of total employment, while in high-income countries, it constitutes around 16% of all employment ( OECD, 2023 ). With the expansion of insecure employment in high-income countries ( Mai et al ., 2023 ), it would seem probable that informal employment will continue to grow.…”
Section: Introductionmentioning
confidence: 99%